Influence of the Pore Generation Method on the Metal Dispersion and Oxidation Activity of Supported Pt in Monolithic Catalysts - Villarroel-Jorquera, M; Villarroel-Jorquera, M (Elsevier, 2016)
The catalytic oxidation activity of structured macro/mesoporous Pt catalysts obtained by the one-step impregnated carbon procedure (ICP) with different binder/support combinations (sepiolite or mixtures with TiO2 or Al2O3) is compared to that of catalysts with the same composition obtained by conventional impregnation of the previously shaped support, with and without activated carbon as pore-generating agent. The superior results of the former are explained in terms of porosity and metal dispersion, estimated by calculation of the platinum apparent molar surface coverage from electrophoretic migration measurements. The big macropores generated reduce the internal diffusion limitations, facilitating the accessibility of the gaseous compounds to the active phase. However, the main improvement for these sepiolite-based monoliths must be mainly attributed to the good Pt dispersion obtained by this method, with metal particles smaller than 10 nm, confirming the role of the activated carbon template not only as a macroporosity generating agent, but also as a dispersant and stabilizer of the metal particles - preventing agglomeration - and as source of CO for in situ reduction of the precursor. In addition, the ICP method minimizes the calcination steps needed for the preparation of the catalyst. © 2015 Elsevier B.V.